Thin‐layer chromatography combined with surface‐enhanced Raman scattering for rapid detection of benzidine and 4‐aminobiphenyl in migration from food contact materials based on gold nanoparticle doped metal‐organic framework. Issue 14 (17th May 2020) - Cai, Guohui; Ge, Kun; Ouyang, Xiaoyan; Hu, Yuling; Li, Gongke
Abstract: In this work, a rapid and sensitive thin‐layer chromatography combined with surface‐enhanced Raman spectroscopy method was established for rapid detection of benzidine and 4‐aminobiphenyl in migration from food contact materials based on Au nanoparticle doped metal‐organic framework. Benzidine and 4‐aminobiphenyl were firstly separated by thin‐layer chromatography to solve the limitation of their overlapping Raman peaks. Then the target molecules were monitored by adding AuNPs/MIL‐101(Cr) on the sample spots. Under the optimum conditions, the concentration of benzidine and 4‐aminobiphenyl can be quantitatively measured in the range of 2.0‐20.0 and1.0‐15.0 μg/L, respectively with good linear relationship, and the limits of detection were 0.21 and 0.23 μg/L, respectively. Furthermore, the developed method was applied to analyze benzidine and 4‐aminobiphenyl in migration of different food contact materials. The recoveries of benzidine and 4‐aminobiphenyl for migration of food contact materials, including paper cups, polypropylene food containers, and polyethylene glycol terephthalate bottles, were 80.6‐116.0 and 80.7‐118% with relative standard deviations of 1.1‐9.1 and 3.1‐9.9%, respectively. Surface‐enhanced Raman scattering detection was performed conveniently in the on‐plate mode without additional elution process. The method shows great potential in rapid monitoring of hazardous substances with overlapping characteristic Raman peaks in food contact materials.